Koebnerization of lichen sclerosus et atrophicus at insulin injection sites - A rare case with dermoscopic features - Tejas Vishwanath; Sunil Ghate; Geeta Shinde; Vikram Lahoria; Binny Binny; Ankita Sonwane (Wolters Kluwer Medknow Publications, 2021)
Lichen sclerosus et atrophicus (LSEA), also known as lichen sclerosus (LS), is a disabling, cosmetically disfiguring condition predominantly affecting the anogenital region of pre- and postmenopausal females. Extragenital LS is relatively less common and occurs predominantly on the trunk and neck. Koebnerization or isomorphic phenomenon is reported occasionally in LS after trauma like radiotherapy. A few case reports describe koebnerization of LS at injection sites. We describe the first such case in India of LS koebnerizing at insulin injection sites with dermoscopic features.